Synchrotron investigations of the nanolime reactivity on biocalcarenite stone surfaces. (30th November 2020) - Macera, L.; Gigli, L.; Daniele, V.; Plaisier, J.R.; Arrizza, L.; Taglieri, G.
Highlights: Synchrotron X-ray diffraction investigations to study the nanolime reactivity in air. The reactivity was analysed both in aqueous and in alcoholic nanolime suspensions. Nanolime reactivity investigated directly on Agrigento biocalcarenite stones. We defined a new parameter called nanolime carbonation rate. Study of the influence of several parameters on the carbonation rate. Abstract: Synchrotron X-ray diffraction investigations were performed to study the reactivity of a nanolime produced by an innovative method based on an ion exchange process, both in aqueous and in alcoholic suspensions. Moreover, for the first time, the nanolime reactivity was investigated both on laboratory glass slides and directly on artistic relevant stones, the biocalcarenite of Agrigento. The results showed that only aqueous suspension exhibits a complete conversion into calcite. The transformation is favoured on porous stone surface, allowing the nanolime suspension to be absorbed and dispersed, increasing the CO2 diffusion.